(untitled) (Agricultural Engineering, 2016)
Improvement of mechanical milking in the aspect of cow's udder health and maintaining correct milking parameters is possible through e.g. constant improvement of the structure of clusters. A cluster with a specific claw with crossing milk connection pipes Flo-Star Max with liners with a round profile of the barrel of DK1X. The objective of the paper was to analyse usefulness of this type of the sitructure of the machine for mechanical milking of cows. Measurements of simulated milking were carried out in a laboratory to the upper milking pipeline at variable mass intensity of liquid flow within 0-8 kg·min-1, for four penetrations of artificial teats of 100, 75, 62, 50 mm at the systemic negative pressure values within 50 to 44 kPa, simultaneous and alternating pulsation and during real milking of cows in a cowshed. Using a multivariate analysis of variance, the impact of independent variables of an experiment on the values of average vacuum of suction, vacuum fluctuations in cycle, average drop of vacuum in a cycle were proved. Analysis of the machine operation in a milking parallel parlour in real mechanical milking conditions and difficulties in placing a machine on the cow's udder as well as violent milk flow were reported and the milk flow of 3.5 kg·min-1 was exceeded with its characteristic balancing in the rhythm of a pulsator.